Upstream Advanced C1. Teachers Book - Evans, V., Edwards, L., Dooly, J. (Newbury Express Publishing, 2008)
Upstream Advanced C1 is a modular secondary-level course for learners of the English language at CEF C1 level. The series combines active English learning with a variety of lively topics presented in themed units.
Keywords: English Practice